2017
DOI: 10.1038/onc.2017.311
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 contributes to the response to PARP inhibitors through its PARP-mediated poly-ADP ribosylation in breast cancer

Abstract: Inhibitors against poly (ADP-ribose) polymerase (PARP) are promising targeted agents currently used to treat BRCA-mutant ovarian cancer and are in clinical trials for other cancer types, including BRCA-mutant breast cancer. To enhance the clinical response to PARP inhibitors (PARPi), understanding the mechanisms underlying PARP inhibitor sensitivity is urgently needed. Here, we show enhancer of zeste homolog 2 (EZH2), an enzyme which catalyzes H3 lysine trimethylation and associates with oncogenic function, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 65 publications
3
72
1
Order By: Relevance
“…Moreover, we found that this association is increased by DNA damage and is not dependent on PARP1 activity. The formation of MUC1-C/ PARP1 complexes could be mediated by EZH2, the activity of which is inhibited by PARP1-directed PARylation (30,53). By contrast, MUC1-C activates EZH2 (29), indicating that MUC1-C and PARP1 may play counteracting roles in the regulation of H3K27me3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that this association is increased by DNA damage and is not dependent on PARP1 activity. The formation of MUC1-C/ PARP1 complexes could be mediated by EZH2, the activity of which is inhibited by PARP1-directed PARylation (30,53). By contrast, MUC1-C activates EZH2 (29), indicating that MUC1-C and PARP1 may play counteracting roles in the regulation of H3K27me3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is overexpressed in many human malignancies, including breast cancer, and its overproduction leads to oncogenesis by decreasing the expression of tumor suppressor genes, suggesting that EZH2 might serve as a candidate for targeted therapy. Yamaguchi and colleges reported that EZH2i sensitized PARPi effect in BRCA defective cancer cells, suggesting that combined inhibition of EZH2 and PARP may be worthwhile to test in clinical trials for patients with BRCA‐defective tumors . Current EZH2 inhibitor development has focused on targeting the SET domain which is required to induce gene silencing by catalyzing H3K27 trimethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi and colleges reported that EZH2i sensitized PARPi effect in BRCA defective cancer cells, suggesting that combined inhibition of EZH2 and PARP may be worthwhile to test in clinical trials for patients with BRCAdefective tumors. 39 Current EZH2 inhibitor development has focused on targeting the SET domain which is required to induce gene silencing by catalyzing H3K27 trimethylation. However, EZH2 could induce an inflammatory response via activating the NF-κB signaling in ER-negative basal-like breast cancer cells, and this effect is independent of histone methyltransferase, suggesting that EZH2 inhibitors targeting the SET domain may be ineffective for TNBC therapy.…”
Section: Tumor Markers and Signaturesmentioning
confidence: 99%
“…Since PARP inhibitors relieve the inhibition of EZH2, increased EZH2 oncogene activity may promote PARP inhibitor resistance. Therefore EZH2 inhibitors may sensitize to PARP inhibition, as demonstrated in preclinical BRCA-deficient model systems [67]. Inhibitors of EZH2 including tazemostat are in early phase clinical development.…”
Section: Other Emerging Combinationsmentioning
confidence: 99%